(3GdGjVGM dfGSN GdbQCf hefShNIs - (3nepqcj Hf CHj WGdH nMoqehT Hf eMeO Hf eNJGQ GdCfOdSj GdbjSj, CHh eMeO,J (B437 (3g` s ((3HOQ GdOjf eMeO Hf Ydi GdbGVi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi de jSHbg TF bGd CHh eMeO eci Gf GMSf eG GfUQaJ Gdjg Gdgee heGdJ Gdjg GdGfaS hJYjJ ajg GdNhGWQ CjGe GdMjGI Ydhe cJGH Gddg Ld PcQg s
(3BNQgG (B:s
(3hJQcfG cKjQkG eeG jJYdb HgPG GdYde EjLGRkG hGNJUGQkG Je s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B286 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B3s
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs